2019
DOI: 10.33259/jlivestsci.2019.91-96
|View full text |Cite
|
Sign up to set email alerts
|

Effects of adding whey and molasses on corn silage quality, growth performance and health of Simmental fattening calves

Abstract: This study was conducted to evaluate the effects of adding whey and molasses on the physical and chemical quality of corn silage, growth performance and health of Simmental fattening calves. This study was carried out in a completely randomized design with 3 treatments and 5 replications for each treatment, and a total of 15 Simmental male calves. Three treatments were included in the study: Treatment 1: corn silage without any additive (control treatment), Treatment 2: corn silage with addition of 10% whey on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 10 publications
2
2
0
Order By: Relevance
“…Whey powder treatment improved silages by decreasing their NDF and ADF contents. These results are in line with the results of previous studies on the effect of WP on the cellulose content in the silage (Dash et al, 1974;Fallah, 2019). According to chemical analyses data, it could be stated that WP used as a fermentation stimulant had a significant effect on the carbohydrate structure of the ensiling material by increasing the rate of NFC versus decreasing the rates of NDF and ADF.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Whey powder treatment improved silages by decreasing their NDF and ADF contents. These results are in line with the results of previous studies on the effect of WP on the cellulose content in the silage (Dash et al, 1974;Fallah, 2019). According to chemical analyses data, it could be stated that WP used as a fermentation stimulant had a significant effect on the carbohydrate structure of the ensiling material by increasing the rate of NFC versus decreasing the rates of NDF and ADF.…”
Section: Discussionsupporting
confidence: 91%
“…Previous studies have generally shown that WP addition to silage improves the fermentation process (Castaño and Villa, 2017;Fallah, 2019). In some studies, it was also observed that addition of WP significantly increases the digestibility of the alfalfa silage, which is believed to be a result of its high lactose content (Dash et al, 1974;Keener, 2019).…”
Section: Discussionmentioning
confidence: 93%
“…Furthermore, the pH value was lower in the case of incubated whey HMG (P = 0.0005). This result is in line with what is expected, considering that the purpose was to use whey as a facilitator of the fermentative process as reported by Fallah (2019). The pH of feed is of paramount importance.…”
Section: Described Phsupporting
confidence: 91%
“…Byproducts from the food industry (e.g., molasses or cheese whey) have also served as alternative additives in ensiling processes [16,17]. Dairy byproducts, such as whey (produced by cheese), have been applied in alfalfa silage [17] and maize silage [18], improving the quality of silages, such as their chemical composition. Acid whey (produced from cheese) was used as a rehydration agent of maize grains, which resulted in the enhancement of the fermentation process and the aerobic stability of the feed after 30 days of ensiling [19].…”
Section: Introductionmentioning
confidence: 99%